Oligonucleotide Immobilisation on Polytyramine-Modified Electrodes Suitable for Electrochemical DNA Biosensors - Tenreiro,A. (2003)
The surface of platinum electrodes was modified by electrochemical polymerisation of tyramine to provide binding sites for covalent specific immobilisation of the nucleotide deoxyguanosine triphosphate (dGTP). The EQCM has been used to monitor the growth of polymeric films, which is clearly demonstrated by the decrease in the frequency, corresponding to a continuous mass increase. The carbodiimide coupling reaction was used to bind the terminal 5 phosphate groups of the dGTP to the available primary amine functions on the polymer surface. The biomolecule immobilisation process was followed by measuring simultaneously the evolution of QC-frequency and open circuit potential. Intrinsic redox signal of guanine base residues provides evidence of the dGTP grafting.